A Follow- up Study of Some Fishing Community Problems around Burullus Lake, Kafr El- Sheikh Governorate, Egypt - Hlil, Abdelhamed Mostafa; Hlil, Hoda Mostafa (Journal of Humanities & Social Sciences, 2022)
The study aimed to follow up some fishing community problems around Burullus Lake by identifying the most important problems facing fishermen at the present time and arranging these problems according to their severity over time. The study was conducted in Kafr El- sheikh Governorate; where three villages were selected randomly from the largest fishing district (Al- Burullus). The three selected villages were overlooking the sea and the lake; they were Al- Burj, Al- Aqoula, and Bar Bahri, on a total sample size of 150 Fishermen. Data was collected using a personal interview questionnaire from each fisherman during November 2021, and 100% of the sample has been targeted. Frequencies, percentages, and average degrees were used in data analysis. The most important results showed that some problems have increased in severity over time. These problems were the presence of reeds, throwing waste in the lake, the presence of Bashnin in the lake, the lack of fishing in light, fishing near bogs, and the difficulty of extracting a carnet for children under 12 years the lack of modern fishing boats, the increase of motors prices in association, the absence of fish canning factories, and the long- distance between markets and the lake. On the other hand, some problems have decreased in severity over time; for example, fry fishing, taking over places in the lake, the absence of an ambulance in the lake, and throwing sewage in the lake, favoritism for some, production smuggling, discrimination in punishment, the difficulty of obtaining boat licenses, yarn price hike, the dispute over fishing places, migration of fishermen to cities and other countries, the lack of snow inside the lake, and underestimating the price by traders.